The Application of Human Relations Theory in Overcoming Resistance to Management Policy: A Literature Study - Ulian Burju Siadari*; Anang Kistyanto; Sanaji Sanaji; Andre Dwijanto Witjaksono (Riwayat: Educational Journal of History and Humanities, 2024)
Resistance to change is one of the main challenges in the implementation of new management policies in organizations. This literature study aims to explore the application of Human Relations Theory as an approach to overcome resistance to a policy. By analyzing the principles of Human Relations Theory and integrating them with change management models, this study provides insights into how building a positive relationship between management and employees, involving employees in the change process, and meeting employees' social and psychological needs can help reduce resistance and increase acceptance of new policies. The research method used is a systematic literature study by collecting and analyzing relevant literature sources. The results of the study show that the application of Human Relations Theory can be an effective strategy in managing resistance to change, especially in the context of the implementation of new management policies.